Preferences of Residents in Four Northern Alberta Communities Regarding Local Post-Secondary Programming - Patrick J. Fahy; Nancy Steel; Patricia Martin (The International Review of Research in Open and Distributed Learning, 2009)
The western Canadian province of Alberta has used some of the proceeds from exploitation of its extraordinary natural resources to make available a range of post-secondary training and education opportunities to residents. While these provisions appear comprehensive, this study examined how well they actually suit the express needs of the residents of remote, Northern areas of the province, many of them Aboriginal. The literature shows that while Aboriginal people are underrepresented in Canada in university enrollments, they are no longer underrepresented in college or other institutions, suggesting that gains have been made for some residents of rural and remote parts of Canada. Further, when Northern residents (especially Aboriginal males) complete advanced training, Statistics Canada reports they are highly successful in employment and income. Access is the pivotal issue, however: leaving the local community to attend training programs elsewhere is often disruptive and unsuccessful. As will be seen, the issue of access arose in this study’s findings with direct implications for distance delivery and support. This study was conducted as part of Athabasca University’s Learning Communities Project (LCP), which sought information about the views and experiences of a broad range of northern Alberta residents concerning their present post-secondary training and education opportunities. The study addresses an acknowledged gap in such information in relation to Canada in comparison with other OECD countries. Results are based on input from 165 individuals, obtained through written surveys (some completed by the researchers in face-to-face exchanges with the respondents), interviews, discussions, and observations, conducted with full-time or part-time residents of the study communities during 2007 and 2008. The four northern Alberta communities studied were Wabasca, Fox Lake, Ft. McKay (sometimes MacKay), and Ft. Chipewyan, totaling just over 6,000 residents. While respondents had varied backgrounds in relation to ...